Critical Analysis of Seblang Tradition of Banyuwangi Osing Tribe Community in Islamic Perspective - Dinda Ayu Prastiwi Berlianti; Sofi Alawiyah Amini (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This article discusses a tradition that is sacred by the Osing Banyuwangi tribal community, namely the Seblang tradition. This research is a field-research that focuses on looking at the Seblang tradition developed in the Osing tribal community using an Islamic perspective. The results of the research reveal that: first, the Seblang tradition developed in the Osing tribal community is a form of cultural preservation which has an element of ritual. Some people consider that the Seblang tradition is a form of shirk in Islam because its rituals are considered to worship Satan and are not in accordance with Islamic values. This can be seen from the procession in the Seblang ritual, the Seblang dance must be led by a shaman to recite a spell and summon spirits which will later possess the Seblang dancers. These spirits are believed by the community to be the spirits of Buyut Kethut, Buyut Ratio, and Buyut Jalil, these spirits are considered the guardians of the village and can bless the Seblang tradition. Second, although the Seblang tradition is considered shirk and worships the devil, but this tradition has an acculturation between local culture and Islamic teachings which can be seen from the prayers read in the tahlilan event before the Seblang tradition begins. Besides, after studied more deeply, the Seblang tradition can also strengthen social solidarity in the communities, reinforce human relationship, as a social unity tool, and increase the sense of nationalism in the cultural preservation.